PENERAPAN MODELPEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII.3 SMP NEGERI 39 PEKANBARU - Rila Mega Putri; Zuhri D '; Suhermi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aimed to improve learning process and mathematics learning outcomes students by applying of Cooperative Learning Type Student Teams Achievement Division (STAD). Subjects of this research are class VII.3 students at SMP Negeri 39 Pekanbaru of 2016/2017, total number of participant are 40 whose academic achievement are heterogen. The research implemented in which consisted of phases. which are planning, implementation, observation, and reflection. By the end of a cycle formative test was held. Data collected through observation and test in the form of formative test. Observation is used to collect teacher and student activities during learning process, test is used to collect mathematic outcomes and will given in form formative test. The research result from the observation form shows that teacher and student activity are good after the treatment implemented. More than half students actively participated in the learning process, as discuss, presented LKS, responded to presenter group, and gave the learning conclusion. The students also tried to solve the quiz from teacher in a great manner.The number of students whose achieved basic score of KKM, formative test I (first cycle), and formativetest II (second cycle) are 16 students (40%), 19 students (47.5%) and 25 students (62,5%). This research shows that implying Student Teams Achievement Division type of cooperative model can improve learning process and increase mathematic learning evaluation for VII.3 Students at SMP Negeri 39 Pekanbaru first semester of 2016/2017 to the basic competence Do the operation on the algebra and Solve the linear equations of one variable.